Field reports, Randall Pinkston, fall 1990 - Pinkston, Randallet al (1990)
Field reports divided by location with an accompanying summary and envelope submitted by Randall Pinkston on October 21, 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed/flatbed